2018
DOI: 10.1111/mice.12348
|View full text |Cite
|
Sign up to set email alerts
|

Multiagent Simulation for Complex Adaptive Modeling of Road Infrastructure Resilience to Sea‐Level Rise

Abstract: Infrastructure systems in coastal areas are exposed to episodic flooding exacerbated by sea-level rise stressors. To enable assessing the long-term resilience of infrastructure to such chronic impacts of sea-level rise, the present study created a novel complex system modeling framework that integrates: (i) stochastic simulation of sea-level rise stressors, based on the data obtained from downscaled climate studies pertaining to future projections of sea level and precipitation; (ii) dynamic modeling of infras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…Instead a new equilibrium state is attained, as seen in other fields such as ecology and economics which inspired developments in the engineering resilience field [ 18 ]. In the proposed study, grounded theories, measures, and methods related to resilience in complex systems [ 10 , 13 , 18 – 22 ] were utilized to build a long-term resilience framework ( Fig 1 ) for civil infrastructure systems under external stressors. The resilience of civil infrastructure system is contingent upon its transformation and adaptation to evolving conditions in the social and environmental sphere [ 21 ].…”
Section: Long-term Resilience Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…Instead a new equilibrium state is attained, as seen in other fields such as ecology and economics which inspired developments in the engineering resilience field [ 18 ]. In the proposed study, grounded theories, measures, and methods related to resilience in complex systems [ 10 , 13 , 18 – 22 ] were utilized to build a long-term resilience framework ( Fig 1 ) for civil infrastructure systems under external stressors. The resilience of civil infrastructure system is contingent upon its transformation and adaptation to evolving conditions in the social and environmental sphere [ 21 ].…”
Section: Long-term Resilience Theoretical Frameworkmentioning
confidence: 99%
“…Based on the existing evidence related to resilience in complex systems [ 10 , 13 , 18 – 22 ] this study, as shown in Fig 1 , identified three important characteristics related to long-term resilience of civil infrastructure systems: (i) external stressors, (ii) internal dynamics, and (ii) performance regime shifts. The following sub-sections explain the three mechanisms which characterize the resilience of complex infrastructure systems.…”
Section: Long-term Resilience Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…However, during the 2011 Christchurch earthquake in New Zealand, although the number of collapsed buildings in the central business district of this city was limited, the functionalities of the area were severely disrupted because the buildings sustained irreparable damage (Kam, Pampanin, & Elwood, 2011;Parker & Steenkamp, 2012;Wikipedia, 2012). For this reason, the con-© 2019 Computer-Aided Civil and Infrastructure Engineering cept of urban building seismic resilience has emerged as one of the most notable topics in order to cope with the aforementioned type of problem (Burton, Deierlein, Lallemant, & Lin, 2015;Franchin & Cavalieri, 2015;Kang, 2018;Mahmoud & Chulahwat, 2018;Wang et al, 2017;Xu, Ouyang, Mao, & Xu, 2019), and simulation methods can be useful tools when dealing with community resilience (Batouli & Mostafavi, 2018;Mostafavi & Ganapati, 2019).…”
Section: Introductionmentioning
confidence: 99%